Comparative evaluation of dentinal tubule penetration and push-out bond strength of new injectable hydraulic calcium disilicate based root canal sealer: A single blinded in vitro study - Aman Verma; Anshul Arora; Sonali Taneja (Journal of Oral Biology and Craniofacial Research, 2024)
Objective: To evaluate and compare dentinal tubule penetration and push-out bond strength of BIO-C ION+, AH Plus and NanoSeal-S using Confocal Laser Scanning Microscopy (CLSM) and Universal Testing Machine (UTM). Materials & method: Sixty human mandibular premolars were prepared using ProTaper Gold till F3. Samples were then divided into 3 groups: Group I (n = 20) BIO-C ION + sealer, Group II (n = 20) AH Plus and Group III (n = 20) NanoSeal-S sealer. Groups were then sub-divided into two sub groups: In Subgroup A (n = 10) samples were obturated using single-cone with 0.1 % Rhodamine B dye and in Subgroup B (n = 10) samples were obturated using single cone. The samples were then transversely sectioned into coronal, middle and apical segments, samples in subgroup A & B were then submitted to CLSM analysis and UTM respectively. Results: The Bond Strength data showed following means (MPa): Group I Subgroup B: (BIO–C ION+) coronal (1.64), middle (1.25), apical (0.93); Group II Subgroup B: (AH Plus) coronal (2.20), middle (1.85) apical (1.38) and Group III Subgroup B: (NanoSeal-S) coronal (1.26), middle (0.94), apical (0.58). The dentinal tubule penetration data showed following means: (μm) Group I Subgroup A (BIO–C ION+) coronal (1184.69), middle (997.03), apical (637.26); Group II Subgroup-A AH Plus (864.14) and NanoSeal-S (495.64). Statistical analysis (two-way ANOVA, Tukey's Post Hoc Test) showed significant difference among sealers (p < 0.001) and root canal thirds (p < 0.001). Conclusion: The results of the study concluded that BIO-C ION + sealer showed maximum dentinal tubule penetration and AH Plus demonstrated maximum push-out bond strength.